On the Self-Intersection Local Time of Subfractional Brownian Motion - Junfeng Liu; Zhihang Peng; Donglei Tang; Yuquan Cang (Abstract and Applied Analysis)
We study the problem of self-intersection local time of d-dimensional subfractional Brownian motion based on the property of chaotic representation and the white noise analysis.